PENGARUH BEBAN KERJA DAN STRES KERJA TERHADAP KINERJA PEKERJA EVENT DI CV. BERLIAN EVENT ORGANIZER SEMARANG - Widayanta, Ardhita Marta; Wirata, I Nengah; Sumadi, I Gede (Journal of Event and Convention Management, 2023)
The development of the event industry organizer in the City of Semarang is quite fast. One such company is Berlian Event Organizer company. The research aims to test the impact of workload and work stress on employee performance in Berlian Event Organizer company. The data was obtained through questionnaires distributed to 54 staff and interviews. The research method is descriptive quantitative. Testing instruments using validity tests and reliability tests. The data is analyzed using the classical assumption test, double linear regression. The results of the analysis can be seen that: 1) workload (X1) has a significant impact on performance of 37.5% on the performance of the employee event 2) work stress (X2) has no significant impact of 11.6% on the work performance of event employees . 3) workload (X1 and work stress X2) have a significant effect of 53% on work performance in event employees in CV. Berlian Event Organizer.